(untitled) (Research, Society and Development, 2022)
The new perception of access to justice is linked to the right of everyone to participate in procedures that are consistent with the national legal order and safeguard fundamental rights. The new approach to access to justice is associated with methods of consensual conflict resolution, among which mediation in a self-composed method of dispute resolution, since the decision-making power in relation to the controversial issue belongs to the conflicting ones and not to a third party. Thus, in order for there to be full openness in obtaining justice through this proper method, the training of the mediator must be guided and oriented so that there is theoretical and practical qualification in his / her performance, aiming at effectively the propagation of the culture of peace in society. This scientific article will study the training of judicial mediators brought by the judicial mediation manual prepared by CNJ in 2016, with a view to concluding with the answer to the question “the training and quality management program of the judicial mediator has the potential to ensure access to justice?”. The methodology of the work is a narrative review of the literature with search, analysis and synthesis of scientific knowledge about the training program and quality management of the judicial mediator. Thus, the entire organization surrounding the mediator is essentially qualifying in terms of the search for the development of full access to justice by society in an equal and satisfactory way.